The Effect of Village Information System Utilisation and Human Resource Capacity on Village Financial Management Accountability - Fazria, Astrid; Br Depari, Fatin Delima; Putri, Novita Aulia; Harahap, Ratu Nazwa; Hutagaol, Juanda Kristian; Irawan, Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to conceptually examine the influence of the utilisation of the Village Information System (SID) and human resource capacity on the accountability of village financial management. Increased village fund allocations require transparent and accountable governance, but the implementation of information technology and the readiness of village officials still face various challenges. This study uses a library research approach with content analysis techniques on scientific literature, regulations, and relevant previous research results. This study is theoretical in nature and does not involve statistical data processing. The results of this study are expected to produce a framework that explains the functional relationship between the utilisation of SID and HR capacity in realising village financial accountability. The utilisation of SID is considered effective if it is supported by adequate human resource capacity as technical implementers. This study is expected to provide a theoretical basis for developing hypotheses in subsequent empirical research and to serve as a reference for village governments in formulating policies to strengthen the transparency and accountability of village financial management based on information technology.